2016
DOI: 10.3390/ijerph13030320
|View full text |Cite
|
Sign up to set email alerts
|

Unmatched Case-Control Study on Late Presentation of HIV Infection in Santiago, Cape Verde (2004–2011)

Abstract: Access to free antiretroviral therapy (ART) in Sub-Saharan Africa has been steadily increasing over the past decade. However, the success of large-scale ART programmes depends on timely diagnosis and early initiation of HIV care. This study characterizes late presenters to HIV care in Santiago (Cape Verde) between 2004 and 2011, and identifies factors associated with late presentation for care. We defined late presentation as persons presenting to HIV care with a CD4 count below 350 cells/mm3. An unmatched cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…In addition, a bivariate logistic regression was performed using a backward stepwise technique to establish the variables related to delayed HIV treatment. Factors that were significant at p < 0.20 were considered for the multivariate model [ 19 ]. The strengths of association were evaluated for factors related to late commencement of ART by means of adjusted odds ratios (AORs) with 95% confidence intervals (CIs).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, a bivariate logistic regression was performed using a backward stepwise technique to establish the variables related to delayed HIV treatment. Factors that were significant at p < 0.20 were considered for the multivariate model [ 19 ]. The strengths of association were evaluated for factors related to late commencement of ART by means of adjusted odds ratios (AORs) with 95% confidence intervals (CIs).…”
Section: Methodsmentioning
confidence: 99%
“…In most studies, the rate of linkage to care was determined based on the time since diagnosis (Reddy et al, 2016;Takah et al, 2016;Billioux et al, 2017;Cholera et al, 2017;Dorward et al, 2017;Franse et al, 2017;Kulkarni et al, 2017;Sanga et al, 2017;Teklu et al, 2017;Boeke et al, 2018;Kayabu et al, 2018;Lopez-Varela et al, 2018;Rane et al, 2018;Rentsch et al, 2018;Maughan-Brown et al, 2019;Hoffman et al, 2020;Maughan-Brown et al, 2021), and late presentation for care was defined as engagement in care at CD4 count <350cells/mm 3 and/or WHO clinical stage III/IV (Gelaw et al, 2015;Haskew et al, 2015;Moreira et al, 2016;Gesesew et al, 2018;Luma et al, 2018). Five studies considered care engagement at CD4 count <200cells/mm 3 as late linkage to care (Honge et al, 2016;Nyika et al, 2016;van der Kop et al, 2016;Gesesew et al, 2018;Lifson et al, 2019) and one study at CD4 count ≤100 cells/mm 3 (Kwobah et al, 2016).…”
Section: Measurementsmentioning
confidence: 99%
“…Fifteen studies reported associations between perceptual or psychosocial factors and late linkage to care (Gelaw et al, 2015;Moreira et al, 2016;Nyika et al, 2016;Reddy et al, 2016;Dorward et al, 2017;Kulkarni et al, 2017;Maheu-Giroux et al, 2017;Sanga et al, 2017;Gesesew et al, 2018;Lopez-Varela et al, 2018;Luma et al, 2018;Rane et al, 2018;Maughan-Brown et al, 2019;Hoffman et al, 2020;Maughan-Brown et al, 2021).…”
Section: Table 1: Characteristics Of Studies Investigating Linkage To...mentioning
confidence: 99%
See 2 more Smart Citations